Film-forming composition

JP2023177929A5Active Publication Date: 2025-03-13KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022090902
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-03
Publication Date
2025-03-13
Estimated Expiration
2042-06-03

AI Technical Summary

Technical Problem

Existing film-forming compositions for electrostatic spraying on skin surfaces, such as those containing water-soluble polymers, tend to dissolve under high temperature or high humidity conditions, compromising adhesion and conformability.

Method used

A film-forming composition comprising a first polymer with low moisture absorption (1% or less) and a second polymer with moderate moisture absorption (5% to 29%) is used to form a film by electrostatic spraying, ensuring stability and conformability even in high temperature and high humidity environments.

Benefits of technology

The composition forms a film with improved adhesion and conformability, maintaining stability and quality over time, even under challenging environmental conditions, and reduces the likelihood of dissolution and twisting, while enhancing the effectiveness of any applied formulations.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a film-forming composition, a film-manufacturing method and a kit for forming a film in order to form an excellently compatible film.SOLUTION: A film-forming composition is electrostatically sprayed on a subject film-forming site directly or indirectly to form a film made of deposit containing fiber. The film-forming composition includes a first polymer and a second polymer. The moisture absorption rate of the first polymer under a high-temperature high-humidity environment (under 40°C 90RH% for 24 hours standing) is 1.0% or less. The moisture absorption rate of the second polymer under a high-temperature high-humidity environment (under 40°C 90RH% for 24 hours standing) is 5% or more and 29% or less. When the mass of the first polymer and the mass of the second polymer in the film-forming composition are M1 and M2 respectively, a value of M2 / (M1+M2) is 0.05 or more and 0.60 or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for film formation, a method for producing a film, and a kit for film formation.

Background Art

[0002] A method of forming a film by an electrostatic spraying method is known. For example, Patent Document 1 describes that a composition containing a volatile substance, a water-insoluble polymer, and an adhesive polymer is directly electrostatically sprayed onto the skin to form a film having good adhesion and transparency to the skin.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0004] In a film formed on a film-forming target site, for example, the skin, a film having good affinity to the skin is desired. In order to improve the affinity of the film to the skin, when a water-soluble polymer compound is used in the composition for film formation, although the affinity is improved, the film may absorb moisture and the film may dissolve. Further, such dissolution of the film tends to occur particularly under conditions such as high temperature or high humidity, and there is room for improvement in the composition for film formation for forming a film by the electrostatic spraying method.

[0005] The problem of the present invention relates to a composition for film formation, a method for producing a film, and a kit for film formation for forming a film having good affinity even under conditions such as high temperature or high humidity.

Means for Solving the Problems

[0006] A coating-forming composition according to one embodiment of the present invention is for forming a coating consisting of a deposit containing fibers by electrostatic spraying directly or indirectly onto a target area for coating. The above-mentioned film-forming composition comprises a first polymer and a second polymer. The first polymer described above has a moisture absorption of 1% or less under high temperature and high humidity conditions (left standing for 24 hours at 40°C and 90RH). The above-mentioned second polymer has a moisture absorption of 5% to 29% under high temperature and high humidity conditions (left standing for 24 hours at 40°C and 90RH).

[0007] A coating manufacturing method according to one embodiment of the present invention is a method for forming a coating on a target area. The above-described method for manufacturing a coating comprises a coating formation step. In the above coating formation process, a coating composition is electrostatically sprayed directly or indirectly onto the area to be coated to form a coating consisting of a deposit containing fibers. The above-mentioned film-forming composition comprises a first polymer and a second polymer. The first polymer described above has a moisture absorption of 1% or less under high temperature and high humidity conditions (left standing for 24 hours at 40°C and 90RH). The above-mentioned second polymer has a moisture absorption of 5% to 29% under high temperature and high humidity conditions (left standing for 24 hours at 40°C and 90RH).

[0008] A coating-forming kit according to one embodiment of the present invention comprises the above-mentioned coating-forming composition and a formulation. The above-mentioned formulation is applied to the skin before or after film formation using the above-mentioned film-forming composition. [Effects of the Invention]

[0009] According to the film-forming composition, film manufacturing method, and film-forming kit of the present invention, a film that adheres well can be obtained even under conditions such as high temperature or high humidity. [Brief explanation of the drawing]

[0010] [Figure 1]This is a schematic diagram showing the configuration of an electrostatic spray device preferably used in the present invention. [Figure 2] This is a schematic diagram showing how a film is formed on the skin by electrostatic spraying using the electrostatic spraying device described above. [Figure 3] This is a schematic diagram of a coating-forming kit according to one embodiment of the present invention. [Figure 4] This graph shows the relationship between the proportion of the second polymer in the film-forming composition and the overall average usability score of the film after storage at high temperature and humidity. [Modes for carrying out the invention]

[0011] This invention relates to improving the adhesion of a coating formed on a target area by electrostatic spraying. The present invention will be described below based on its preferred embodiments.

[0012] In this invention, a coating is formed by directly or indirectly applying a coating-forming composition containing predetermined components to the target area via electrostatic spraying. In this invention, by configuring the film-forming composition to contain predetermined components, the adhesion of the film to the target area for film formation can be improved. By using the electrostatic spraying method, it is possible to form a coating of deposited fibers (so-called nanofibers) with a fiber diameter on the order of nanometers. The target site for film formation is typically human skin, but it may also be human teeth, gums, skin, teeth, gums of non-human mammals, or plant surfaces such as branches and leaves. The following explanation will use an example of film formation on human skin. Furthermore, while the following explanation describes an example of directly forming a film on human skin by electrostatic spraying, it is also possible to form a film on the skin by first forming a film on an applicator, which is an intermediate film-forming object, by electrostatic spraying, and then transferring the film to the skin. This method of forming a film on an intermediate film-forming object and then transferring the film to the film-forming area is referred to as "indirectly forming a film on the film-forming area by electrostatic spraying." In this specification, the target site for finally forming a film is referred to as the "film-forming target site". Therefore, when the film is transferred to the skin after once forming the film on the applicator, the film-forming target site is the skin. In this specification, the "user" refers to a person to whom a film adheres to the skin. The "caregiver" refers to a person who performs at least a part of the application operation of the preparation and the film formation operation on behalf of the user.

[0013] The film formed using the film-forming composition of the present invention can be suitably used for wounds and abnormal conditions from the skin surface to the basal layer of the epidermal site. Specifically, it promotes tissue regeneration, promotes basement membrane regeneration, activates epidermal cell proliferation, epidermal cell epithelialization (promotes keratinization), improves barrier function, improves moisture content, improves scaling, suppresses crust formation, suppresses inflammation, suppresses post-inflammatory pigmentation, etc. It can be suitably used for improving the skin condition and treating wounds. The film is formed on a wound healing target site such as the skin of a human having symptoms such as scaling and inflammation, or damaged skin after laser treatment, etc., and protects the skin. By forming a film on the skin, the film can protect the skin from external stimuli and foreign substances, and it is also possible to efficiently heal symptoms such as scaling and inflammation and damage after laser treatment. The film-forming composition of the present invention is typically used in combination with a preparation (described later). By using the preparation in combination, the preparation can be held between the fibers by utilizing the capillary force of the fibers of the film. Thereby, while protecting the skin, a situation can be created in which the preparation acts on the skin efficiently and effectively. The preparation can be applied to the skin before or after film formation by electrostatic spraying. In the following description, an example of applying and using the preparation before film formation will be given. Note that the film may be used alone without using it in combination with the preparation. By forming the film on the skin, the skin can be protected from external stimuli and foreign substances. The following will be described in detail.

[0014] <Film-forming composition> The inventors focused on the moisture absorption of the polymer used in the film-forming composition under high-temperature and high-humidity environments, and by formulating a film-forming composition by blending a first polymer with a relatively low moisture absorption and a second polymer with a relatively high moisture absorption under high-temperature and high-humidity environments, it was found that a film that is less affected by the use environment and has good adhesion can be formed using the film-forming composition. The following will be described in detail.

[0015] Here, "good adhesion" means that the user actually feels that the formed film adheres firmly to the skin (the site where the film is to be formed), and when touching the skin on which the film is formed with the pulp of the finger or the palm of the hand, etc., a state where the entire body part (the pulp of the finger or the palm of the hand) touching feels uniformly adsorbed to the skin with adhesiveness.

[0016] The film-forming composition of the present invention comprises a first polymer having a moisture absorption of 1% or less under high-temperature and high-humidity environments, a second polymer having a moisture absorption of more than 1% and 40% or less under high-temperature and high-humidity environments, and a solvent. The solvent evaporates during the film-forming process, and the film is composed of the first polymer and the second polymer. Incidentally, the film-forming composition is composed of the first polymer, the second polymer and the solvent, but may contain other components other than these. The first polymer is the part that forms the core of the film. The second polymer contributes to the modification of the surface of the fibers constituting the film.

[0017] [Method for Measuring the Moisture Absorption of Polymer under High-Temperature and High-Humidity Environments] In this specification, the moisture absorption of the polymer under high-temperature and high-humidity environments is measured by the measurement method described below. 1 g of the polymer to be measured is left standing in an incubator at 40 °C and 90% RH (high-temperature and high-humidity environment) for 24 hours to apply a high-temperature and high-humidity load to the polymer to be measured. The initial weight of the polymer to be measured is defined as the weight measured immediately after leaving it undisturbed for 1 minute in an environment of 25°C and 50% RH before applying a high temperature and high humidity load. The weight measured immediately after leaving the polymer to be measured in an environment of 25°C and 50% RH for 1 minute immediately after removing it from the incubator after applying the high temperature and high humidity load is defined as the weight measured immediately after. The moisture absorption of the polymer to be measured is then calculated using the following formula (1). Humidity absorption = (Weight after high temperature and humidity load - Initial weight) / Initial weight × 100 (%) …(1) In this specification, unless otherwise specified, "humidity absorption" means "humidity absorption under high temperature and high humidity conditions."

[0018] [First Polymer] From the viewpoint of creating a coating that is less affected by the usage environment and can easily maintain good quality, the first polymer has a moisture absorption of 1% or less, more preferably 0.9% or less. Also, from the same viewpoint, it is preferable that the moisture absorption is 0.1% or more, more preferably 0.6% or more.

[0019] In addition to the aforementioned hygroscopic properties, the physical properties of the first polymer can also be explained from the perspective of water insolubility. Specifically, it is preferable that the first polymer is a polymer that, when 1 g of polymer is weighed and immersed in 10 g of deionized water under an environment of 1 atmosphere and 23°C, more than 0.5 g of the immersed polymer does not dissolve after 24 hours.

[0020] More specifically, from the viewpoint of creating a coating that is easy to maintain good quality, it is more preferable to use one or more polymers selected from polyvinyl butyral resin, polyurethane resin, and polylactic acid as the first polymer, and it is even more preferable to use polyvinyl butyral resin.

[0021] [Second Polymer] The second polymer has a moisture absorption of more than 5%, preferably 6.5% or more, from the viewpoint of good compatibility and reducing wrinkles and air bubbles in the film formed on the skin. Similarly, from the viewpoint of suppressing nozzle clogging during electrostatic spraying, it has a moisture absorption of 29% or less, preferably 28.4% or less. The moisture absorption of the second polymer is more than 5% and 29% or less, preferably 6.5% or more and 28.4% or less.

[0022] As the second polymer, it can contain one or more polymers selected from polyvinylpyrrolidone, a copolymer of polyvinylpyrrolidone, polyalkylene glycol, and a silicone structure-containing copolymer. From the viewpoint of improving the adherence of the film formed on the skin, it is preferable to use a polymer that contains one or more polymers selected from polyvinylpyrrolidone copolymer and polyalkylene glycol. Furthermore, the content ratio of one or more polymers selected from polyvinylpyrrolidone, polyvinylpyrrolidone copolymers, polyalkylene glycols, and silicone structure-containing copolymers relative to the total amount of the second polymer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more, from the viewpoint of improving the adherence of the film formed on the skin.

[0023] Examples of polyvinylpyrrolidone copolymers include vinyl acetate-vinylpyrrolidone copolymer, vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, diethyl sulfate, and vinylcaprolactam-vinylpyrrolidone-dimethylaminopropylmethacrylamide-methacryloylaminopropyllauryldimonium chloride copolymer. From the viewpoint of improving the adhesion of the film formed on the skin, it is preferable to use vinyl acetate-vinylpyrrolidone copolymer.

[0024] Vinyl acetate-vinylpyrrolidone copolymer is a copolymer obtained by polymerizing vinyl acetate and vinylpyrrolidone, and the polymer has a structure based on vinyl acetate and a structure based on vinylpyrrolidone. Here, if the structure based on vinyl acetate is denoted as VP and the structure based on vinylpyrrolidone as VA, the ratio of VP to VA (VP:VA) in the vinyl acetate-vinylpyrrolidone copolymer in the present invention is preferably in the range of VP:VA = 20:80 to 80:20, and more preferably in the range of VP:VA = 25:75 to 65:35, from the viewpoint of improving the adherence of the film formed on the skin. Note that the ratio in this item refers to the molar ratio, and the amount of residual monomer relative to the initial monomer composition can be calculated by gas chromatography.

[0025] As a more specific example, the following commercially available products can be used as polyvinylpyrrolidone and its copolymers. Product Name: PVA / VA E735 (Ashland Japan Co., Ltd.) Product Name: PLASDONE® S630 (Ashland Japan Co., Ltd.) Product Name: PVA / VA E535 (Ashland Japan Co., Ltd.) Product Name: PVA / VA E335 (Ashland Japan Co., Ltd.) Product Name: Gafquat (Registered Trademark) 734 (Ashland Japan Co., Ltd.) Product Name: Aquastyle300N (Ashland Japan Co., Ltd.)

[0026] Examples of polyalkylene glycols include polyethylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol. From the viewpoint of improving the adhesion of the film formed on the skin, it is preferable to use polyoxyethylene polyoxypropylene glycol.

[0027] The average number of moles of ethylene oxide added to polyoxyethylene polyoxypropylene glycol is preferably 5 to 200, more preferably 10 to 30, from the viewpoint of good compatibility and reduction of wrinkles and air bubbles in the film formed on the skin. Similarly, the average number of moles of propylene oxide added is preferably 5 to 100, more preferably 10 to 30, from the same viewpoint. The average number of moles of ethylene oxide added can be calculated, for example, by the method described in "JIS K 0070-1992 7.1 Neutralization titration method," and the average number of moles of propylene oxide added is 1 This can be determined using 1H-NMR.

[0028] As a more specific example, the following commercially available products can be used as polyethylene glycol adducts. Product name: Pronon (registered trademark) 124P (NOF Co., Ltd.)

[0029] As a more specific example, the following commercially available products can be used as silicone structure-containing copolymers. Product Name: Silicone KF-6011 (Shin-Etsu Chemical Co., Ltd.)

[0030] [solvent] The solvent contains one or more selected from monohydric alcohols and ketones. Monohydric alcohols and ketones are volatile substances. From the viewpoint of ensuring good adhesion of the formed film, the solvent preferably contains one or more selected from ethanol, isopropyl alcohol, and butyl alcohol as monohydric alcohols, and more preferably contains ethanol. From a similar viewpoint, the solvent preferably contains acetone as a ketone. The type of solvent used can be appropriately determined depending on the type of first polymer, and a solubilizer for the first polymer can be used as the solvent. For example, when polyvinyl butyral resin or polyurethane resin is used as the first polymer, ethanol can be used as the solvent. When polylactic acid is used as the first polymer, acetone can be used as the solvent.

[0031] When ethanol is used as the solvent, the ethanol content in the solvent is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, relative to the total amount of the solvent, from the viewpoint of high volatility and compatibility with the formed film. Furthermore, it is preferably 100% by mass or less, and more preferably 95% by mass. In addition, the ethanol content in the solvent is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 95% by mass or less, relative to the total amount of the solvent.

[0032] Furthermore, the solvent may contain water. In the examples described later, we give an example in which 99-degree synthetic alcohol (Nippon Synthetic Alcohol Co., Ltd.), which is an anhydrous alcohol with an ethanol content of 99.5% by volume or more, is used as the solvent. However, since ethanol easily absorbs moisture from the air, the ethanol content will not be 100% by volume. Therefore, when using the above-mentioned 99-degree synthetic alcohol as a solvent, the solvent will contain moisture. Furthermore, in the description of the ethanol content in the solvent mentioned above, ethanol refers to the anhydrous alcohol, 99% synthetic alcohol (Nippon Synthetic Alcohol Co., Ltd.).

[0033] The water content in the solvent is preferably 0.2% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.4% by mass or more, relative to the total amount of the solvent, from the viewpoint of compatibility with the formed film. Furthermore, it is preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0034] When forming a nanofiber coating using electrostatic spraying, the solvent is evaporated to form the nanofibers, so it is preferable that the main component of the solvent be a volatile substance. The volatile substance preferably has a vapor pressure of 0.01 kPa or more and 106.66 kPa or less at 20°C, more preferably 0.13 kPa or more and 66.66 kPa or less, even more preferably 0.67 kPa or more and 40.00 kPa or less, and even more preferably 1.33 kPa or more and 40.00 kPa or less.

[0035] In a film formed using the film-forming composition of the present invention, the content of the first polymer is preferably 40% by mass or more, more preferably 48% by mass or more, even more preferably 54% by mass or more, even more preferably 60% by mass or more, even more preferably 64% by mass or more, and from the viewpoint of good compatibility and reducing wrinkles and air bubbles in the film formed on the skin, and also preferably 98% by mass or less, more preferably 89% by mass or less, even more preferably 85% by mass or less, even more preferably 82% by mass or less, and even more preferably 79% by mass or less. Furthermore, the content of the first polymer is preferably 40% by mass or more and 98% by mass or less, more preferably 48% by mass or more and 89% by mass or less, even more preferably 54% by mass or more and 85% by mass or less, even more preferably 60% by mass or more and 82% by mass or less, and even more preferably 64% by mass or more and 79% by mass or less.

[0036] In a film formed using the film-forming composition of the present invention, the content of the second polymer is preferably 2% by mass or more, more preferably 12% by mass or more, even more preferably 15% by mass or more, even more preferably 18% by mass or more, and even more preferably 21% by mass or more, and also preferably 60% by mass or less, more preferably 52% by mass or less, even more preferably 46% by mass or less, even more preferably 40% by mass or less, and even more preferably 34% by mass or less. Furthermore, the content of the second polymer is preferably 2% by mass or more and 60% by mass or less, more preferably 12% by mass or more and 52% by mass or less, even more preferably 15% by mass or more and 46% by mass or less, even more preferably 18% by mass or more and 40% by mass or less, and even more preferably 21% by mass or more and 34% by mass or less.

[0037] [Mass ratio (blending ratio) of the first polymer and the second polymer in the film-forming composition] From the viewpoint of forming a coating that is less affected by the usage environment and blends well, it is preferable to define the blending ratio of the first polymer, which has relatively low moisture absorption in high-temperature and high-humidity environments, and the second polymer, which has relatively high moisture absorption, as follows. In the film-forming composition, the proportion of the second polymer to the total polymer of the first polymer and the second polymer combined (hereinafter sometimes simply referred to as "the proportion of the second polymer") is preferably 0.05 or more, more preferably 0.11 or more, even more preferably 0.15 or more, even more preferably 0.18 or more, even more preferably 0.21 or more, and from the viewpoint of good compatibility and reducing wrinkles and air bubbles in the film formed on the skin, it is also preferably 0.60 or less, more preferably 0.52 or less, even more preferably 0.46 or less, even more preferably 0.40 or less, even more preferably 0.38 or less, and even more preferably 0.34 or less. Furthermore, the proportion of the second polymer to the total polymer when the first polymer and the second polymer are combined is preferably 0.05 to 0.60, more preferably 0.11 to 0.52, even more preferably 0.15 to 0.46, even more preferably 0.18 to 0.40, even more preferably 0.21 to 0.38, and even more preferably 0.21 to 0.34. The proportion of the second polymer can be determined by the following formula (2), where M1 is the mass (content) of the first polymer in the film-forming composition and M2 is the mass (content) of the second polymer. The proportion of the second polymer = M2 / (M1+M2) …(2)

[0038] In this embodiment, the film-forming composition is composed of a mixture of a first polymer, a second polymer, and a solvent. The solvent evaporates during the film-forming process, and the film is composed of the first polymer and the second polymer.

[0039] The film-forming composition of the present invention is composed of a first polymer with relatively low moisture absorption and a second polymer with relatively high moisture absorption in the above-mentioned proportions. This improves the moisture resistance of the film formed using the film-forming composition. For example, even in high-temperature and high-humidity usage environments such as bathrooms and changing rooms, the film formed on the skin is less likely to absorb moisture, dissolve, and become wrinkled, resulting in a film with a stable shape and maintained quality. Furthermore, when the area to be covered is a wound on the skin, the cover is in a state where it easily absorbs exudate, and the humidity at the area where the cover is formed is high. However, by improving the moisture resistance of the cover, the phenomenon of the cover dissolving due to exudate is less likely to occur, and the quality of the cover can be stably maintained. Furthermore, when the target area for film formation is the oral cavity, such as teeth and gums, which are high-humidity environments, the film is in a state where it easily absorbs saliva. However, by improving the moisture resistance of the film, the phenomenon of the film dissolving due to saliva is less likely to occur, and the quality of the film can be stably maintained. Thus, the film formed using the film-forming composition of the present invention maintains its quality and stable film shape even in high-temperature or high-humidity environments.

[0040] In addition, by including a second polymer, the adhesion of the coating to the skin can be improved, resulting in a coating that maintains good adhesion even in high-temperature or high-humidity environments, and can maintain good adhesion continuously regardless of the usage environment. Furthermore, because it adheres well to the skin, it is less likely for the film to wrinkle or for air bubbles to be trapped, resulting in a natural appearance where the boundary between skin with and without the film is indistinguishable, making the presence of the film almost imperceptible. Furthermore, the coating formed using the coating-forming composition of the present invention adheres firmly to the skin, even on uneven skin surfaces such as wounds, by conforming to the irregularities of the skin, thus reducing the likelihood of sensory discomfort on the skin.

[0041] Furthermore, the inclusion of the second polymer improves the compatibility between the coating and the formulation, ensuring that the formulation is present throughout the entire coating formed on the skin. This allows for prolonged and effective contact between the formulation, held between the fibers, and the skin during use. As a result, the penetration of the formulation into the skin is further enhanced, improving the effectiveness of the formulation on the skin. Furthermore, the formed coating exhibits excellent moisture resistance even under conditions of high temperature or high humidity, making it less susceptible to environmental influences and allowing the film shape to be easily maintained stably. Therefore, the formulation can be stably retained between the fibers for extended periods, further enhancing the skin-adhering effects of the formulation.

[0042] Thus, by using the film-forming composition of the present invention, it is possible to form a film of stable quality that is less affected by the usage environment and can stably maintain a good film shape and good adhesion over a long period of time.

[0043] <About electrostatic spraying> A coating is formed by electrostatically spraying a film-forming composition and depositing fibers onto the skin. The electrostatic spraying method involves applying a positive or negative high voltage to a film-forming composition to charge it, and then spraying the charged composition toward an object. The sprayed film-forming composition spreads through the air, repeatedly becoming finer due to Coulomb repulsion, and during this process, or after adhering to the area to be coated, the volatile solvent evaporates, forming a film on the surface of the area to be coated.

[0044] [Electrostatic spray device] Figure 1 is a schematic diagram showing the configuration of an electrostatic spray device preferably used in the present invention. As shown in Figure 1, the electrostatic spray device 10 comprises a low-voltage power supply 11, a high-voltage power supply 12, an auxiliary electrical circuit 13, a microgear pump 14 as a liquid supply pump, a container 15, a nozzle 16, a conduit 17, a flexible conduit 18, and a current limiting resistor 19. Note that the liquid supply pump can be replaced with a piston pump instead of a gear pump, and the nozzle and pump may be replaceable.

[0045] The low-voltage power supply 11 generates a voltage of several volts to over ten volts. To improve the portability of the electrostatic spray device 10, the low-voltage power supply 11 is preferably composed of one or more batteries. Using batteries as the low-voltage power supply 11 also has the advantage of being easily replaceable as needed. Instead of batteries, an AC adapter or the like can also be used as the low-voltage power supply 11.

[0046] The high-voltage power supply 12 is connected to the low-voltage power supply 11 and includes an electrical circuit (not shown) that boosts the voltage generated by the low-voltage power supply 11 to a high voltage. The boosting electrical circuit generally consists of a transformer, a capacitor, and semiconductor elements.

[0047] The auxiliary electrical circuit 13 is interposed between the low-voltage power supply 11 and the high-voltage power supply 12, and has the function of adjusting (amplifying) the voltage of the low-voltage power supply 11 to ensure stable operation of the high-voltage power supply 12. Furthermore, the auxiliary electrical circuit 13 has the function of controlling the rotational speed of the motor provided in the microgear pump 14. By controlling the rotational speed of the motor, the amount of film-forming composition supplied from the container 15 to the microgear pump 14 is controlled. A switch SW is installed between the auxiliary electric field 13 and the low-voltage power supply 11. The electrostatic spray device 10 can be operated / stopped by switching the SW on and off.

[0048] The nozzle 16 is made of various conductive materials, including metal, and its outer circumference is covered with a non-conductive material such as plastic, rubber, or ceramic. The nozzle 16 is shaped to allow the film-forming composition to be dispensed from its tip. A minute space through which the film-forming composition flows is formed inside the nozzle 16 along its longitudinal direction. The cross-sectional size of this minute space is preferably 100 μm or more and 1000 μm or less in diameter. The nozzle 16 is connected to the microgear pump 14 via a conduit 17. The conduit 17 may be made of a conductive or non-conductive material. The nozzle 16 is electrically connected to the high-voltage power supply 12, making it possible to apply a high voltage to the nozzle 16. In this case, to prevent an excessive current from flowing if a human body directly touches the nozzle 16, the nozzle 16 and the high-voltage power supply 12 are electrically connected via a current-limiting resistor 19.

[0049] The container 15 contains the coating-forming composition. Preferably, the container 15 is a replaceable cartridge type. The container 15 is connected to the microgear pump 14 via a flexible conduit 18. The microgear pump 14 functions as a supply device that delivers the film-forming composition contained in the container 15 to the nozzle 16. The microgear pump 14 operates by receiving power from the low-voltage power supply 11. The microgear pump 14, under the control of the auxiliary electrical circuit 13, supplies a predetermined amount of the coating composition to the nozzle 16.

[0050] Figure 2 shows an example of the use of the electrostatic spray device 10 described above. In the example shown in Figure 2, the electrostatic spray device 10 is a handy type with dimensions that allow it to be held in one hand. The electrostatic spray device 10 has a cylindrical housing 20, and all of the components shown in Figure 1 are housed within the housing 20. Note that the shape of the housing 20 is not limited to a cylindrical shape, and can typically be a shape and dimensions that are easy to hold in one hand. A nozzle (not shown) is positioned at one end 10a in the longitudinal direction of the housing 20. The nozzle is positioned so as to be convex toward the skin side, with the direction of discharge of the film-forming composition 1 aligned with the longitudinal direction of the housing 20. This makes it difficult for the film-forming composition to adhere to the housing 20, allowing for stable film formation.

[0051] <Method for manufacturing coatings using electrostatic spraying> A preferred method for producing a coating according to the present invention comprises a formulation application step and a coating formation step. The formulation application step may be performed before or after the coating formation step.

[0052] [Formulation Application Process] The formulation application process involves applying the formulation to the skin. The formulation is applied by the user or assistant, primarily to the area where film formation is to occur. The formulation has a different composition from the film-forming composition, preferably does not contain the first polymer of the present invention, and preferably is applied to the skin by a method other than electrostatic spraying. Preferably, the formulation has functions such as moisturizing, anti-inflammatory, antiseptic, and topical hemorrhoid treatment. The formulation may be selected as appropriate depending on the skin symptoms. Examples of formulations will be described later. The formulation can be applied to the skin in liquid, cream, foam, or mist form for ease of application. Typically, the formulation is applied to the skin before film formation to improve adhesion between the film and the skin. Applying the formulation before the film-forming process makes the sprayed film-forming composition adhere more strongly due to electrostatic force, and also improves the transparency of the sprayed film-forming composition. Improved transparency makes the presence of the film less visually apparent, resulting in a natural, skin-like appearance without any unnatural feel. On the other hand, if the formulation application process is performed after the film formation process, the film formed by electrostatic spraying becomes more easily absorbed by the formulation, resulting in increased adhesion to the skin and further improved transparency.

[0053] Here, applying a formulation to the skin refers to a state in which the formulation adheres to, is applied to, carries, or is fixed to a target area on the skin. The means by which the formulation is applied to the skin are not particularly limited. For example, it may be spread using fingers, a brush, or other tools, or it may be sprayed using a sprayer or the like.

[0054] [Film formation process] The film formation process involves using the electrostatic spraying device 10 to electrostatically spray a film-forming composition directly onto the skin to form a film consisting of deposits containing fibers. By using the formulation and coating together, the capillary force of the fibers forming the coating prevents the formulation from being unevenly distributed and allows it to spread, while also retaining the formulation between the fibers and / or on the fiber surface.

[0055] The coating manufacturing method using the electrostatic spray device 10 is as follows: As shown in Figure 2, the user U, that is, the person who will be forming a coating on their skin using electrostatic spraying, holds the electrostatic spraying device 10 in their hand and points one end 10a of the electrostatic spraying device 10, where the nozzle (not shown) is located, towards the area to be coated with electrostatic spraying. Figure 2 shows the state in which one end 10a of the electrostatic spraying device 10 is pointed towards the inside of the user U's forearm. In this state, the switch of the electrostatic spraying device 10 is turned on and electrostatic spraying is performed. When the electrostatic spray device 10 is powered on, an electric field is generated between the nozzle and the skin. In the embodiment shown in Figure 2, a positive high voltage is applied to the nozzle, and the skin becomes the negative electrode. When an electric field is generated between the nozzle and the skin, the film-forming composition at the tip of the nozzle is polarized by electrostatic induction, and its tip becomes cone-shaped. From the tip of the cone, charged droplets of the film-forming composition are discharged into the air along the electric field toward the skin. As the solvent evaporates from the charged film-forming composition discharged into the space, the charge density on the surface of the film-forming composition becomes excessive, and it spreads into the space while repeatedly becoming finer due to Coulomb repulsion, and reaches the skin. While being discharged into the space, the volatile substance, which is the solvent, is volatilized from the film-forming composition, and the polymer (first polymer and second polymer), which is the solute and has film-forming ability, is solidified, and while being stretched and deformed by the potential difference, fibers are formed, and these fibers are deposited on the surface of the skin to form a film. Once the electrostatic spraying is complete, the power to the electrostatic spraying device 10 is turned off. This eliminates the electric field between the nozzle and the skin.

[0056] During the electrostatic spraying process, a high potential difference is generated between the nozzle and the skin. However, because the impedance is very high, the current flowing through the human body is extremely small. For example, the inventors have confirmed that the current flowing through the human body during the electrostatic spraying process is several orders of magnitude smaller than the current flowing through the human body due to static electricity generated in normal daily life.

[0057] When forming a fiber deposit by electrostatic spraying, the thickness of the fibers, expressed as a circular diameter, is preferably 10 nm or more, more preferably 50 nm or more. It is also preferably 3000 nm or less, and more preferably 1000 nm or less. In this way, by forming a coating using electrostatic spraying, it is possible to form a coating consisting of nanometer-order fibers. The thickness of a fiber can be measured, for example, by observing it under a scanning electron microscope (SEM) at a magnification of 10,000 times, removing defects (fiber clumps, fiber intersections, droplets) from the two-dimensional image, selecting 10 fibers at random, drawing lines perpendicular to the longitudinal direction of the fibers, and directly reading the fiber diameter.

[0058] [Examples of formulations] The formulation preferably contains one or more selected from water, polyols, and oils that are liquid at 20°C.

[0059] Water-containing formulations include, for example, water, aqueous solutions, and aqueous dispersions. Other water-containing formulations include lotions, emulsions such as O / W emulsions and W / O emulsions, compositions having a lamellar structure, cosmetic creams, and aqueous solutions thickened with thickeners. From the viewpoint of moisturizing properties and ensuring good adhesion of the film to the skin, compositions having a lamellar structure are preferred.

[0060] When the formulation contains a polyol, examples of the polyol include alkylene glycols such as ethylene glycol, propylene glycol, 1,3-propanediol, and 1,3-butanediol; polyalkylene glycols such as diethylene glycol, dipropylene glycol, polyethylene glycol, and polypropylene glycol; and glycerin derivatives such as glycerin, diglycerin, and triglycerin. From the viewpoint of ensuring good adhesion of the film to the skin, a polyol that is liquid at 20°C is preferred.

[0061] When the formulation contains a polyol, the polyol content in the formulation is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more, from the viewpoint of improving the compatibility of the film attached to the skin, and also 40% by mass or less, preferably 30% by mass or less, and even more preferably 20% by mass or less. Furthermore, the polyol content in the formulation is preferably 3% by mass or more and 40% by mass or less, more preferably 5% by mass or more and 30% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less.

[0062] When a formulation contains an oil that is liquid at 20°C (hereinafter, this oil is also referred to as "liquid oil"), examples of oils that are liquid at 20°C include straight-chain or branched hydrocarbon oils, ester oils, higher alcohols of branched or unsaturated fatty acids, and silicone oils.

[0063] Examples of the above-mentioned hydrocarbon oils include liquid paraffin, squalane, squalene, n-octane, n-heptane, cyclohexane, light isoparaffin, and liquid isoparaffin, with liquid paraffin and squalane being preferred from the viewpoint of usability.

[0064] Furthermore, polar oils that are liquid at 20°C can also be preferably used as the above-mentioned liquid oil. Examples include ester oils, higher alcohols of branched or unsaturated fatty acids, and silicone oils. These liquid oils can be used individually or in combination of two or more.

[0065] Examples of the above-mentioned ester oils include esters consisting of a linear or branched fatty acid and a linear or branched alcohol or polyhydric alcohol. Specifically, these include isopropyl myristate, cetyl octanoate, octyldodecyl myristate, isopropyl palmitate, butyl stearate, hexyl laurate, myristyl myristate, decyl oleate, hexyldecyl dimethyloctanoate, cetyl lactate, myristyl lactate, lanolin acetate, isocetyl stearate, isocetyl isostearate, cholesteryl 12-hydroxystearylate, ethylene glycol di-2-ethylhexanoate, dipentaerythritol fatty acid ester, and monoisostearate N -Alkyl glycol, neopentyl glycol dicaprate, diisostearyl malate, glyceryl di-heptylundecanoate, trimethylolpropane tri-2-ethylhexanoate, trimethylolpropane triisostearate, pentaerythritol tetra-2-ethylhexanoate, glyceryl tri-2-ethylhexanoate, trimethylolpropane triisostearate, cetyl 2-ethylhexanoate, 2-ethylhexyl palmitate, diethylhexyl naphthalenedicarboxylate, benzoic acid (carbon 12~ 15) Alkyl, Cetearyl Isononanoate, Caprylic / Capric Triglyceride, Butylene Glycol Dicaprylate / Capric Triglyceride, Glyceryl Trilaurate, Glyceryl Trimyristate, Glyceryl Tripalmitate, Glyceryl Triisostearate, Glyceryl Tri-2-Heptyl Undecanoate, Glyceryl Tribehenate, Glyceryl Tri-2-Heptyl Undecanoate, Glyceryl Triisostearate, Glyceryl Coconut Oil Fatty Acid, Methyl Castor Oil Fatty Acid, Oleyl Oleate, Palmitate Examples include 2-heptyl undecyl mitate, diisobutyl adipate, 2-octyldodecyl N-lauroyl-L-glutamic acid, di-2-heptyl undecyl adipate, ethyl laurate, di-2-ethylhexyl sebacate, 2-hexyldecyl myristate, 2-hexyldecyl palmitate, 2-hexyldecyl adipate, diisopropyl sebacate, di-2-ethylhexyl succinate, triethyl citrate, 2-ethylhexyl paramethoxycinnamate, and tripropylene glycol dipivalate. Furthermore, the liquid oil may include vegetable oils or animal oils containing ester oils. Examples of liquid oils containing ester oils include vegetable oils such as jojoba oil, olive oil, macadamia nut oil, meadowfoam oil, castor oil, safflower oil, sunflower oil, avocado oil, canola oil, apricot kernel oil, rice germ oil, and rice bran oil, as well as animal oils such as liquid lanolin.

[0066] Examples of higher alcohols include liquid higher alcohols with 12 to 20 carbon atoms, specifically isostearyl alcohol and oleyl alcohol.

[0067] Examples of silicone oils include dimethylpolysiloxane, dimethylcyclopolysiloxane, methylphenylpolysiloxane, methylhydrogenpolysiloxane, and higher alcohol-modified organopolysiloxane.

[0068] When the formulation contains liquid oil, the liquid oil content in the formulation is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass, from the viewpoint of improving the adhesion of the film to the skin, and also 10% by mass or less, preferably 6% by mass or less, and even more preferably 4% by mass or less. Furthermore, the liquid oil content in the formulation is preferably 1% by mass or more and 10% by mass or less, more preferably 1.5% by mass or more and 6% by mass or less, and even more preferably 2% by mass or more and 4% by mass or less.

[0069] Furthermore, the formulation may also contain solid lipids, and from the viewpoint of improving the compatibility of the film attached to the skin, it is preferable to include pseudo-ceramides. In this invention, pseudo-ceramides include those also called natural (animal) ceramides, human-type ceramides, and synthetic ceramides. For example, the cosmetic ingredient name is cetyl PG hydroxyethyl palmitamide, and the quasi-drug ingredient name is N-(hexadecyloxyhydroxypropyl)-N-hydroxyethylhexadecanamide, or hexadecyloxy PG hydroxyethyl hexadecanamide (abbreviated name).

[0070] <Coating Formation Kit> As shown in Figure 3, the film-forming kit 2 of the present invention comprises a container 15 filled with the above-mentioned film-forming composition and a container 3 filled with the formulation. The container 15 is, for example, a replaceable cartridge type. The user or caregiver can set the container 15 in the electrostatic spray device 10 and use it.

[0071] <Other configurations>

[0072] [Moisture absorption of the coating] The moisture absorption of the film formed using the film-forming composition is preferably 1% to 10%, more preferably 2% to 9%, and even more preferably 3% to 7%, from the viewpoint of improving the moisture resistance and adhesion of the film. The moisture absorption of the films in each of the examples described later is shown in Tables 1 to 4. The moisture absorption of the coating is calculated using a weighted average as shown in equation (3) below. In formula (3), M1 is the mass (content) of the first polymer in the coating, M2 is the mass (content) of the second polymer in the coating, A1 is the moisture absorption of the first polymer, and A2 is the moisture absorption of the second polymer. The moisture absorption is calculated using formula (1) above. The mass ratio of the first polymer to the second polymer in the coating is the same as the mass ratio of the first polymer to the second polymer in the coating composition. Moisture absorption of the coating = (A1 × M1 + A2 × M2) / (M1 + M2) …(3)

[0073] [Relationship between the moisture absorption of the first polymer and the second polymer] From the viewpoint of improving the moisture resistance and compatibility of the film formed using the film-forming composition, it is preferable that the difference in moisture absorption between the first polymer and the second polymer be 5% to 30%, more preferably 7% to 16%.

[0074] Although the present invention has been described above based on its preferred embodiments, the present invention is not limited to the above embodiments.

[0075] <Examples> The present invention will be further described below with reference to examples. However, the scope of the present invention is not limited to these examples.

[0076] <<Test Example 1: Examination of the blending ratio of the first polymer and the second polymer>> In Examples 1 to 12, coatings were formed using coating compositions with varying mass ratios (blending ratios) of the first polymer and the second polymer, and the usability of the coatings before and after high temperature and humidity conditions was evaluated. Furthermore, the moisture resistance of cast films (also called polymer coatings) formed using the first and second polymers blended in the mass ratios specified in each example was evaluated. It should be noted that although the fibers of the cast films evaluated for moisture resistance were not nanofibers, it was confirmed that equivalent moisture resistance evaluation results could be obtained as if nanofibers were used.

[0077] [Preparation of coating-forming compositions] For the film-forming compositions of Examples 1 to 12, mixtures of the following first polymer, second polymer, and solvent were prepared. (First polymer) Polyvinyl butyral resin (product name: S-REC® BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated using the above formula (1) was 0.9%. (Second polymer) As the second polymer, a vinyl acetate / vinylpyrrolidone copolymer (product name: PLASDONE® S630, Ashland Japan Co., Ltd.) was used. The moisture absorption of this polymer, calculated using the above formula (1), was 16.8%. (solvent) As the solvent, 99% synthetic alcohol (Nippon Synthetic Alcohol Co., Ltd.), which is an anhydrous alcohol with an ethanol content of 99.5% by volume or more, was used. In the following description of the examples, this anhydrous alcohol will be referred to as "ethanol." As mentioned above, since ethanol readily absorbs moisture from the air, strictly speaking, the solvent contains water. Ethanol was mixed into the film-forming composition at a ratio of 93% by mass.

[0078] In each of Examples 1 to 12, the mass ratio of the first polymer to the second polymer in the film-forming composition (first polymer:second polymer) is as follows. (Example 1) 71.4:28.6 (Example 2) 95.2:4.8 (Example 3) 90.9:9.1 (Example 4) 87.0:13.0 (Example 5) 83.3:16.7 (Example 6) 76.9:23.1 (Example 7) 66.7:33.3 (Example 8) 62.5:37.5 (Example 9) 55.6:44.4 (Example 10) 50.0:50.0 (Example 11) 45.5:54.5 (Example 12) 41.7:58.3

[0079] [Evaluation of usability] Five expert panelists evaluated the usability of the coatings formed using the coating-forming compositions of each example, both before and after storage at high temperature and humidity. In evaluating the film-forming composition before storage at high temperature and humidity, expert panelists electrostatically sprayed the film-forming composition onto the inside of their forearms using the electrostatic spray device 10 under the following film-forming conditions to form a film, and then evaluated the film according to the evaluation method described below. To evaluate the film-forming composition after high-temperature and high-humidity storage, a fiber sheet was first prepared by electrostatically spraying the film-forming composition onto a base layer using the electrostatic spraying device 10 to form a film. This fiber sheet was then packaged in a breathable packaging material and left to stand in an incubator at 40°C and 90% RH (high-temperature and high-humidity environment) for 24 hours. The expert panelists removed the fiber sheet from the breathable packaging material after high-temperature and high-humidity storage, positioned the fiber sheet so that the film was in direct contact with the inside of their forearm, and transferred the film by removing the base layer, thereby forming a film on their skin. Rayon nonwoven fabric (product name: Omi Kenshi 45, Omi Kenshi Co., Ltd.) was used as the base layer.

[0080] The conditions for film formation by electrostatic spraying are as follows: Applied voltage: 30kV Distance between nozzle and skin: 130mm Discharge volume of film-forming composition: 4 mL / h Environment: 25℃, 30%RH

[0081] [Evaluation items and evaluation methods] The usability was evaluated based on three criteria: familiarity, appearance, and wrinkles / air bubbles. The expert panelists evaluated the adhesion of the film formed on the skin, the appearance of the film, and the presence of wrinkles and air bubbles in the film. The evaluation was conducted without applying the formulation before or after film formation. Five expert panelists evaluated each evaluation item on a 5-point scale from 1 to 5 according to the following evaluation criteria. Based on the overall average score, the usability of the coating was evaluated on a 4-point scale from A to D according to the usability evaluation criteria below. Table 1 shows the overall average score of the usability of the coatings formed using the coating-forming compositions of each example, both before and after high-temperature and high-humidity storage, as well as the evaluation results based on that score, and the average score for each evaluation item.

[0082] (Item evaluation criteria) 5 points...Excellent 4 points... Good 3 points…average 2 points... Bad 1 point... Very bad

[0083] (Usability evaluation criteria) A: 4.5 ≤ Overall Average Score ≤ 5.0 B: 4.0 ≤ Overall average score < 4.5 C: 3.0 ≤ Overall Average Score < 4.0 D: Overall average score < 3.0

[0084] [Evaluation of moisture resistance of cast film] The moisture resistance of the cast film was evaluated as follows: 0.35 g of the polymer to be evaluated (a mixture of the first and second polymers according to the formulation ratios of each example) was dissolved in 4.65 g of ethanol to prepare 5 g of polymer solution. This polymer solution was prepared in a ratio of 7% by mass of polymer and 93% by mass of ethanol. The polymer solution was placed in a 5 cm square plastic scheele and dried at room temperature for 72 hours to evaporate the ethanol and prepare a cast film. Next, the prepared cast film was left to stand in an incubator at 40°C and 90% RH (high temperature and high humidity environment) for 24 hours. The weight change rate of the cast film before and after standing in the high temperature and high humidity environment was calculated. Based on this weight change rate, the hygroscopicity of the cast film was evaluated on a four-point scale from A to D as follows. The evaluation results are shown in Table 1. A: 0% ≤ Weight change rate ≤ 5% B: 5% < Weight change rate ≤ 10% C: 10% < Weight change rate ≤ 15% D: 15% < Weight change rate

[0085] [Table 1]

[0086] Figure 4 is a graph created based on Table 1, showing the relationship between the proportion of the second polymer (horizontal axis) and the overall average usability score of the coating after high-temperature and high-humidity storage (vertical axis).

[0087] As shown in Table 1 and Figure 4, when the proportion of the second polymer in the film-forming composition was 0.05 to 0.60, the film's compatibility evaluation before and after high-temperature and high-humidity storage was 3 or higher, and the usability evaluation was B or higher, indicating good performance.

[0088] <<Test Example 2: Investigation of the Second Polymer, Part 1>> In Examples 1 (the same as Example 1 of Test Example 1), 13, and 14, film-forming compositions were prepared using the same blending ratio of the first polymer and the second polymer, but with the second polymer being a material with different moisture absorption properties. The usability of the films formed using these film-forming compositions under the same formation conditions as in Test Example 1, both before and after high temperature and high humidity, was evaluated using the same method as in Test Example 1. Furthermore, the moisture resistance of cast films formed using the first and second polymers in the formulation ratios of each example in the same manner as in Test Example 1 was evaluated using the same method as in Test Example 1. Furthermore, as Comparative Example 1, a film-forming composition containing only the first polymer was prepared, and the usability of the film formed using this film-forming composition was evaluated. In addition, the moisture resistance of the cast film formed using only the first polymer was evaluated. Table 2 shows the overall average score of the usability of the coatings formed by the coating-forming compositions of each example and comparative example before and after high-temperature and high-humidity storage, the evaluation results based on that score, the average score for each evaluation item, and the evaluation results for the cast film.

[0089] [Preparation of coating-forming compositions] For the film-forming compositions of Examples 1, 13, and 14, mixtures of the following first polymer, second polymer, and solvent were prepared. In preparing these mixtures, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. Furthermore, a mixture of the following first polymer and solvent was prepared as a film-forming composition for Comparative Example 1. The second polymer was not included in this film-forming composition. (First polymer) Polyvinyl butyral resin (product name: S-REC® BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated using the above formula (1) was 0.9%. (Second polymer) The following were used as the second polymer in each example. ((Example 1)) Vinyl acetate / vinylpyrrolidone copolymer (product name: PLASDONE® S630, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 16.8%. ((Example 13)) Diethyl sulfate of vinylpyrrolidone dimethylaminoethyl methacrylate copolymer (product name: Gafquat734, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 28.4%. ((Example 14)) Vinylcaprolactam / vinylpyrrolidone / dimethylaminopropylmethacrylamide / methacryloylaminopropyllauryldimonium chloride copolymer (Aquastyle300N Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by formula (1) above was 19.8%. (solvent) Ethanol was used as the solvent. Ethanol was mixed into the film-forming composition at a ratio of 93% by mass.

[0090] [Table 2]

[0091] <<Test Example 3: Investigation of the Second Polymer, Part 2>> In Examples 1 (the same as Example 1 of Test Example 1) and Examples 15-17, vinyl acetate / vinylpyrrolidone copolymers with different compositional ratios of vinylpyrrolidone (VP) and vinyl acetate (VA) were used as the second polymer, and the blending ratio of the first and second polymers was the same. The usability of the films formed under the same formation conditions as in Test Example 1, both before and after high temperature and humidity, was evaluated using the same method as in Test Example 1. Furthermore, the moisture resistance of the cast films formed using the first and second polymers of each example was evaluated using the same method as in Test Example 1. Table 3 shows the overall average score of the usability of the coatings formed by the coating-forming compositions of each example before and after high-temperature and high-humidity storage, the evaluation results based on that score, the average score for each evaluation item, and the evaluation results for the cast film.

[0092] [Preparation of coating-forming compositions] As the coating compositions for Examples 1, 15-17, a mixture of the first polymer, the second polymer, and the solvent shown below was prepared. In preparing this mixture, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. (First polymer) Polyvinyl butyral resin (product name: S-REC® BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated using the above formula (1) was 0.9%. (Second polymer) The following were used as the second polymer in each example. (Example 1) The vinyl acetate / vinylpyrrolidone copolymer (product name: PLASDONE® S630 (composition ratio VP:VA = 60:40), Ashland Japan Co., Ltd.) had a moisture absorption of 16.8% calculated using the above formula (1). (Example 15) The moisture absorption of the vinyl acetate / vinylpyrrolidone copolymer (product name: PVP / VA E735 (composition ratio VP:VA = 70:30), Ashland Japan Co., Ltd.) calculated using the above formula (1) was 26.2%. (Example 16) The moisture absorption of the vinyl acetate / vinylpyrrolidone copolymer (product name: PVP / VA S535 (composition ratio VP:VA = 50:50), Ashland Japan Co., Ltd.) calculated using the above formula (1) was 14.6%. (Example 17) The moisture absorption of vinyl acetate / vinylpyrrolidone copolymer (product name: PVP / VA E335 (composition ratio VP:VA = 30:70), Ashland Japan Co., Ltd.) was 12.0% as calculated by the above formula (1). (solvent) Ethanol was used as the solvent. Ethanol was mixed into the film-forming composition at a ratio of 93% by mass.

[0093] [Table 3]

[0094] <<Test Example 4: Investigation of the Second Polymer, Part 3>> Examples 1 (the same as Example 1 of Test Example 1), 18 and 19, and Comparative Examples 2 and 3 were prepared by using the same blending ratio of the first polymer and the second polymer, but using materials with different hygroscopic properties for the second polymer. The usability of the films formed using these film-forming compositions under the same formation conditions as in Test Example 1, both before and after high temperature and high humidity, was evaluated using the same method as in Test Example 1. Furthermore, the moisture resistance of the cast films formed using the first and second polymers of each example and comparative example in the same manner as in Test Example 1 was evaluated using the same method as in Test Example 1. Table 4 shows the overall average score of the usability of the coatings formed by the coating-forming compositions of each example and comparative example before and after high-temperature and high-humidity storage, the evaluation results based on that score, the average score for each evaluation item, and the evaluation results for the cast film. In Table 4, a "-" in the usability column indicates that the coating dissolved and the evaluation could not be performed.

[0095] [Preparation of coating-forming compositions] For the film-forming compositions of Examples 1, 18, and 19, and Comparative Examples 2 and 3, a mixture of the first polymer, the second polymer, and the solvent shown below was prepared. In preparing this mixture, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. (First polymer) Polyvinyl butyral resin (product name: S-REC® BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated using the above formula (1) was 0.9%. (Second polymer) The following were used as the second polymer in each example and comparative example. (Example 1) The vinyl acetate / vinylpyrrolidone copolymer (product name: PLASDONE® S630, Ashland Japan Co., Ltd.) had a moisture absorption of 16.8% calculated using the above formula (1). (Example 18) Polyoxyethylene (20) polyoxypropylene (20) glycol (product name: Pronon 124P, NOF Corporation) The moisture absorption of the polymer calculated using the above formula (1) was 8.5%. (Example 19) The moisture absorption of PEG-11 methyl ether dimethicone (product name: Silicone KF6011, Shin-Etsu Chemical Co., Ltd.) calculated using the above formula (1) was 6.5%. ((Comparative Example 2)) Polyethylene glycol (product name: PEG400, Wako Pure Chemical Industries, Ltd.) This polyethylene glycol is a polymer with an average molecular weight of 360 to 440. The moisture absorption of this polymer, calculated using the above formula (1), was 45.6%. ((Comparative Example 3)) Polyethylene glycol (product name: PEG1450, Sanyo Chemical Industries, Ltd.) This polyethylene glycol is a polymer with an average molecular weight of 1450. The moisture absorption of this polymer, calculated using the above formula (1), was 42.0%. (solvent) Ethanol was used as the solvent. Ethanol was mixed into the film-forming composition at a ratio of 93% by mass.

[0096] [Table 4]

[0097] Furthermore, the following primer solution (formulation) formulation is disclosed as an example of a formulation that can be applied before and after the film formation process. <Primer liquid formulation> Pseudo-ceramide 1% by mass Glycerin fatty acid ester 0.34% by mass Cetyl alcohol 0.34% by mass Dimethylpolysiloxane 2% by mass Glycerin 10% by mass 1,3-Butanediol 3% by mass Distearyldimonium chloride 0.4% by mass Polyoxyethylene sorbitan monostearate (20 E.O.) 0.2% by mass Succinic acid 0.005% by mass Methyl parahydroxybenzoate 0.2% by mass The mixture was balanced with purified water so that the total percentage reached 100% by mass. [Explanation of Symbols]

[0098] 1...Film forming composition

Claims

1. A coating composition for forming a coating comprising a fiber-containing deposit by electrostatically spraying the composition directly or indirectly onto a target site for coating, comprising: The coating composition is A first polymer having a moisture absorption of 1% or less in a high temperature and high humidity environment (when left standing for 24 hours at 40°C and 90% RH); A second polymer having a moisture absorption of 5% to 29% in a high temperature and high humidity environment (left to stand for 24 hours at 40°C and 90% RH); Includes Composition for film formation.

2. When the mass of the first polymer in the composition for forming a coating is M1 and the mass of the second polymer is M2, the value of M2 / (M1+M2) is 0.05 or more and 0.60 or less. The coating composition according to claim 1 .

3. The second polymer includes one or more polymers selected from polyvinylpyrrolidone, copolymers of polyvinylpyrrolidone, polyalkylene glycols, and copolymers containing a silicone structure. The coating composition according to claim 1 or 2.

4. The second polymer includes one or more polymers selected from vinyl acetate-vinylpyrrolidone copolymer, vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer diethyl sulfate, vinylcaprolactam-vinylpyrrolidone-dimethylaminopropyl methacrylamide-methacryloylaminopropyl lauryldimonium chloride copolymer, polyoxyethylene polyoxypropylene glycol, and PEG-11 methyl ether dimethicone. The coating composition according to claim 3 .

5. The first polymer is one or more polymers selected from the group consisting of polyvinyl butyral resin, polyurethane resin, and polylactic acid. The coating composition according to claim 1 or 2.

6. The composition for forming a coating film further contains one or more selected from a monohydric alcohol and a ketone. The coating composition according to claim 1 or 2.

7. The site to be coated is human skin. The coating composition according to claim 1 or 2.

8. A coating manufacturing method for forming a coating on a coating formation target portion, comprising the steps of: The method includes a coating forming step of electrostatically spraying a coating composition directly or indirectly onto a target portion to form a coating made of a deposit containing fibers, The coating composition is A first polymer having a moisture absorption of 1% or less in a high temperature and high humidity environment (when left standing for 24 hours at 40°C and 90% RH); A second polymer having a moisture absorption of 5% to 29% in a high temperature and high humidity environment (left to stand for 24 hours at 40°C and 90% RH); Includes Coating manufacturing method.

9. A preparation application step of applying a preparation to the site to be coated before or after the coating formation step. Further comprising The method for producing a coating according to claim 8.

10. The coating composition according to claim 1 or 2, a preparation to be applied to the site to be coated before or after coating formation using the coating composition; A coating formation kit comprising: